The Bordetella effector protein BteA induces host cell death by disruption of calcium homeostasis - Zmuda, Martin; Sedlackova, Eliska; Pravdova, Barbora; Cizkova, Monika; Dalecka, Marketa; Cerny, Ondrej; Allsop, Tania Romero; Grousl, Tomas; Malcova, Ivana; Kamanova, Jana (mBio, 2024)
Bordetella pertussis is the causative agent of whooping cough in humans, a disease that has recently experienced a resurgence. In contrast, Bordetella bronchiseptica infects the respiratory tract of various mammalian species, causing a range of symptoms from asymptomatic chronic carriage to acute illness. Both pathogens utilize type III secretion system (T3SS) to deliver the effector protein BteA into host cells. Once injected, BteA triggers a cascade of events leading to caspase 1-independent necrosis through a mechanism that remains incompletely understood. We demonstrate that BteA-induced cell death is characterized by the fragmentation of the cellular endoplasmic reticulum and mitochondria, the formation of necrotic balloon-like protrusions, and plasma membrane permeabilization. Importantly, genome-wide CRISPR-Cas9 screen targeting 19,050 genes failed to identify any host factors required for BteA cytotoxicity, suggesting that BteA does not require a single nonessential host factor for its cytotoxicity. We further reveal that BteA triggers a rapid and sustained influx of calcium ions, which is associated with organelle fragmentation and plasma membrane permeabilization. The sustained elevation of cytosolic Ca2+ levels results in mitochondrial calcium overload, mitochondrial swelling, cristolysis, and loss of mitochondrial membrane potential. Inhibition of calcium channels with 2-APB delays both the Ca2+ influx and BteA-induced cell death. Our findings indicate that BteA exploits essential host processes and/or redundant pathways to disrupt calcium homeostasis and mitochondrial function, ultimately leading to host cell death.IMPORTANCEThe respiratory pathogens Bordetella pertussis and Bordetella bronchiseptica exhibit cytotoxicity toward a variety of mammalian cells, which depends on the type III secretion effector BteA. Moreover, the increased virulence of B. bronchiseptica is associated with enhanced expression of T3SS and BteA. However, the molecular mechanism underlying BteA cytotoxicity is elusive. In this study, we performed a CRISPR-Cas9 screen, revealing that BteA-induced cell death depends on essential or redundant host processes. Additionally, we demonstrate that BteA disrupts calcium homeostasis, which leads to mitochondrial dysfunction and cell death. These findings contribute to closing the gap in our understanding of the signaling cascades targeted by BteA.
Keywords: buněčná smrt; mitochondrie; Endoplasmic Reticulum; endoplazmatické retikulum; host cell death mechanism; vápník; Type III Secretion Systems; sekreční systém typu III; Host-Pathogen Interactions; Bordetella; Cell Death; Bacterial Proteins; Calcium; effector protein BteA; Bordetella pertussis; Bordetella bronchiseptica; zvířata; Humans; homeostáza; interakce hostitele a patogenu; Mitochondria; type III secretion system (T3SS); calcium homeostasis; Homeostasis; bakteriální proteiny; lidé; Animals